Cyberpedagogy: Innovations In Digital Education And Their Impact On The Learning Process - Bekchonova Shoira Bazarbayevna (Frontline Social Sciences and History Journal, 2026)
This article examines the theoretical foundations and practical mechanisms of cyber-pedagogy within digital education. Using literature review, content analysis, comparative analysis, and case study methods, the study identifies learner-centered instruction, collaborative learning, and purposeful technological integration as core principles of cyber-pedagogy. The findings indicate that interactive platforms, multimedia resources, and online assessment enhance student engagement, motivation, and knowledge retention. At the same time, challenges such as the digital divide, insufficient digital literacy, and limited methodological preparedness of teachers persist. The paper concludes with practical recommendations for effective implementation of cyber-pedagogy in educational environments.